Rancangan Sistem Pembuatan Kompos dengan Tempat Sampah Berbasis IOT (Internet of Things) - Baaskara, I Dewa Gede Surya; Eka Karyawati, Anak Agung Istri Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025, 2025)
Increased awareness of the importance of household organic waste management has driven the development of innovation in waste treatment. This paper deals with the design and implementation of intelligent garbage cans that can turn household trash, especially food and vegetable residues, into high-quality composite materials. The system uses efficient aerobic composting technology to accelerate the organic decomposition process. Through automatic monitoring and optimum setting of environmental conditions, these garbage cans can produce fertile compost in a short time. In addition to providing practical solutions to household garbage management, the importance of keeping the environment on its own is also emphasized. Through awareness of the negative impact of waste on the environment, individuals can play an active role in promoting sustainable and environmentally friendly practices.